Exploring the Persuasion Effects of Threatening Content in COVID-19 Advertising: The Roles of Threat Intensity and Sensation Seeking on Consumer Attitudes - Quan Xie; Tianjiao (Grace) Wang (Politeknik Negeri Bandung, 2023)
The COVID-19 pandemic has resulted in a wave of advertising activities advocating care for the community in a time of crisis. These COVID-19 ads often feature threatening depictions of the crisis as a persuasion strategy. Hence, the present study explores the persuasion effects of COVID-19 advertising by focusing on threat persuasion. Specifically, by adopting an online experiment with 724 U.S. participants, this study investigates how the threat intensity of crisis depictions featured in COVID-19 ads (low vs. medium vs. high) interact with individual differences in sensation-seeking in order to impact ads and brand attitudes, through the mediating pathways of positive moral emotions (warmth and gratitude) and corporate social responsibility (CSR) authenticity. The results reveal that the high-threat crisis depiction generates the lowest warmth and ad attitudes, whereas the medium-threat crisis depiction yields the strongest gratitude and better brand attitudes than the low-threat crisis depiction, but only for low sensation seekers (LSS). Also, for LSS, exposure to the medium-threat (versus low-threat) crisis depiction increases their gratitude, which leads to higher CSR authenticity, and, eventually results in more favorable ad or brand attitudes. On the contrary, for high sensation seekers, threat intensity does not have an indirect effect on the ad or brand attitudes via warmth, gratitude, and CSR authenticity.